(untitled) (International Journal of Engineering and Computer Science, 2017)
Software maintenance is very important and time consuming task which require a lot of parameters to be taken care during the whole cycle of maintenance of software. The software maintenance engineer has used various cost estimation models in their research work like COCOMO-I, COCOMO-II, SLIM, SEERSEM and FP. The problem with these models is that they require the complete data and information making any decision and benchmark. Therefore the cost of software maintenance varies with types and complexity of the software under the maintenance. We have identified the various factors which effects the cost of the software maintenance. The various cost estimation models require a lots of metrics and only after calculating the complete parameters, then only the software cost can be determined.